Diagnosis and Management of Adrenal Crisis in 46XX Congenital Adrenal Hyperplasia Infant - Rochmah, Nur; Faizi, Muhammad; Kusumastuti, Neurinda Permata; Samadhi, Leonardo Ferryanto Mak; Deakandi, Wika Yuli (Folia Medica Indonesiana, 2022)
Highlight: • The diagnosis and therapy of Congenital Adrenal Hyperplasia (CAH) children with Adrenal crisis (AC) case report. • Adrenal crisis (AC) is a life-threatening emergency that contributes to the high death rate of children with adrenal insufficiency. • The early detection and prompt treatment can improve the outcomes of patients with CAH and AC. Abstract: Adrenal crisis is the acute complication of the patient with congenital adrenal hyperplasia. Congenital adrenal hyperplasia (CAH) is a rare condition. Children with CAH commonly come to the emergency room due to acute complications. The condition has high mortality and thus needs early recognition. Newborn screening for CAH in Indonesia is not routinely performed and has not been suggested yet. The purpose of this case report was to report a case of adrenal crisis in a congenital adrenal hyperplasia patient focused on diagnosis and therapy. A female, 10 months old infant, was admitted to the emergency department with a chief complaint of a decrease of consciousness for 3 hours before admission and frequent vomiting since born. On physical examination, there was clitoromegaly. Laboratory showed 17-OH progesterone: 173 ng/dL (7-77 ng/dL) and karyotyping: 46 XX. Management of adrenal crisis is a stress dose of hydrocortisone and rehydration. Education is the key to optimal outcomes and normal growth and development.